Contribution of histone variants to aneuploidy: a cancer perspective - Ragusa, Denise; Vagnarelli, Paola (Frontiers in Genetics, 2023)
Histone variants, which generally differ in few amino acid residues, can replace core histones (H1, H2A, H2B, and H3) to confer specific structural and functional features to regulate cellular functions. In addition to their role in DNA packaging, histones modulate key processes such as gene expression regulation and chromosome segregation, which are frequently dysregulated in cancer cells. During the years, histones variants have gained significant attention as gatekeepers of chromosome stability, raising interest in understanding how structural and functional alterations can contribute to tumourigenesis. Beside the well-established role of the histone H3 variant CENP-A in centromere specification and maintenance, a growing body of literature has described mutations, aberrant expression patterns and post-translational modifications of a variety of histone variants in several cancers, also coining the term 'oncohistones'. At the molecular level, mechanistic studies have been dissecting the biological mechanisms behind histones and missegregation events, with the potential to uncover novel clinically-relevant targets. In this review, we focus on the current understanding and highlight knowledge gaps of the contribution of histone variants to aneuploidy, and compiled a database (HistoPloidyDB) of histone gene alterations linked to aneuploidy in cancers of the TCGA project.